The collapse of water, sanitation, and hygiene systems in Gaza: Public health implications and global security perspectives - Tika Pustika Fersari; Jana Abu Salha (Indonesian Red Crescent Humanitarian Journal, 2025)
Since the escalation of large-scale conflict in October 2023, severe destruction of civilian infrastructure has occurred in the Gaza Strip, including the collapse of Water, Sanitation, and Hygiene (WASH) systems. This breakdown has rapidly triggered a public health emergency with short-, medium-, and long-term consequences. Short-term impacts included marked increases in infectious diseases such as diarrhea and hepatitis A, acute malnutrition, and elevated risks to maternal and child health. Medium-term impacts involved ecological degradation through groundwater contamination and sanitation system failure, which in turn contributed to rising clean-water prices and widening socio-economic inequalities, disproportionately affecting women and children. Long-term impacts generated intergenerational risks, including the potential emergence of a “lost generation” due to stunting and increased global health security concerns associated with transboundary disease spread. Comparative evidence from Yemen, Syria, Sub-Saharan Africa, and Indonesia (Aceh and Papua) indicates similar epidemiological patterns, in which WASH destruction is associated with cyclical epidemics, malnutrition, and deepening structural vulnerability. Using a descriptive qualitative approach based on a review of academic literature, international organizational reports, policy documents, and credible media sources, this study systematically examines the implications of WASH system collapse for public health in Gaza during the ongoing genocide. The analysis develops a conceptual framework that positions the WASH crisis not only as a humanitarian concern but also as a public health emergency with regional and global ramifications. On this basis, the study concludes that effective WASH reconstruction should be prioritized as a humanitarian and global health security strategy and integrated with nutrition, maternal–child health, and social protection programs. The findings also underscore the need for comprehensive international policy responses and reinforce arguments for recognizing the protection of WASH infrastructure as a fundamental human right in armed conflict.